Can the inclusion of black soldier fly (Hermetia illucens) in diet affect the flesh quality/nutritional traits of rainbow trout (Oncorhynchus mykiss) after freezing and cooking?. (17th February 2019) - Secci, Giulia; Mancini, Simone; Iaconisi, Valeria; Gasco, Laura; Basto, Ana; Parisi, Giuliana
Abstract: Physical and chemical parameters of rainbow trout fillets were tested during 120 days of frozen storage and following cooking. The fillets were obtained from rainbow trout-fed diets where dietary fishmeal was substituted with Hermetia illucens meal at 0, 25 and 50% inclusion levels, corresponding to control (C), Hi25, and Hi50 diets. Variations in quality traits of fillets emerged after 30 days of frozen storage, however they remained almost unchanged for the other 90 days. Increasing levels of H. illucens did not affect pH, shear stress, colour and water holding capacity of fillets. Saturated fatty acids were highly present in Hi50 samples, the polyunsaturated and some monounsaturated ones were higher in C than Hi50, whereas Hi25 always assumed intermediate contents in raw and cooked samples. A medium substitution at the 25% seemed to be the most practical application of insect meal in order to not modify too much the fillets characteristics. Graphical Abstract: